A Thermodynamic View on Solvent Effect of Selected S2N Reaction - Dabbit, O.; Kadri, S.; Wasif, S.; khalil, A.; B. Salama, Salama (Asian Journal of Chemistry, 2010)
The present work describes the role of solvents on the kinetics and thennodynamics of closely related S2N reactions of primary, secondary and tertiary iodoalkanes in pure and mixed solvents.